The Unique Metabolic Characteristics of Bone Marrow Adipose Tissue - Li, Yujue; Meng, Yang; Yu, Xijie (Frontiers in Endocrinology, 2019)
Bone marrow adipose tissue (MAT) is distinct from white adipose tissue (WAT) or brown adipose tissue (BAT) for its location, feature and function. As a largely ignored adipose depot, it is situated in bone marrow space and resided with bone tissue side-by-side. MAT is considered not only as a regulator of bone metabolism through paracrine, but also as a functionally particular adipose tissue that may contribute to global metabolism. Adipokines, inflammatory factors and other molecules derived from bone marrow adipocytes may exert systematic effects. In this review, we summary the evidence from several aspects including development, distribution, histological features and phenotype to elaborate the basic characteristics of MAT. We discuss the association between bone metabolism and MAT, and highlight our current understanding of this special adipose tissue. We further demonstrate the probable relationship between MAT and energy metabolism, as well as glucose metabolism. On the basis of preliminary results from animal model and clinical studies, we propose that MAT has its unique secretory and metabolic function, although there is no in-depth study at present.